Evaluation of three : dimensional basal heave - Poon, Cedric Guan Hui (2015)
Basal heave is an important factor that must be taken into consideration in the design of braced excavation. There are various softwares available for the calculation of the factor of safety(FS) of basal heave. In this study, the finite element programs Plaxis 2D and 3D will be used to determine the stability of basal heave and also to investigate the influence of the length of excavation on the FS. Several parameters that will affect the stability of basal heave were taken into account. These parameters are the length of excavation (L), the stiffness of the wall (EI) and the wall penetration below the base of excavation (D). A total of 24 cases were analyzed with different parameters. Six of these were analyzed using Plaxis 2D and the remaining 18 were analyzed using Plaxis 3D. In Plaxis 3D, all 3 parameters were taken into account whereas in Plaxis 2D, only 2 of the parameters, excluding L, were taken into account. The result shows that factor of safety for both Plaxis 2D and Plaxis 3D increases with decreasing L, increasing D and EI. An attempt for comparison was made between the factor of safety for 2D and 3D to investigate the capability in which to determine the length of excavation is significant enough to avoid using 3D. However due to time constraint, only coarse mesh was analyzed with Plaxis 3D.